(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
This article analyzes the state of development of small business and private entrepreneurship, its share in macroeconomic indicators such as GDP, export and industry. Also, proposals on the main ways of developing small business and private entrepreneurship were requested.